ANTESEDEN INTENSI WIRAUSAHA BERDASARKAN SOCIAL COGNITIVE CAREER THEORY - Kurnia, Dede; Ngasifudin, Muhammad (Fakultas Ekonomi dan Bisnis, UNTAN, 2021)
ABSTRACTThis study aims to determine and analyze the mediating effect of entrepreneurial outcome expectations and entrepreneurial attitude on the influence of entrepreneurial self-efficacy on entrepreneurial intention. This study uses a quantitative approach with explanatory survey methods. The data collection tool in this study uses a questionnaire. In contrast, in determining the number of samples, this study applied convenience sampling so as obtain 75 young people in district Sukaresik, Tasikmalaya. The analysis technique carried out in this study was regression-based Serial Multiple Mediators using Macro Process software developed by Andrew F. Hayes. The result showed that entrepreneurial self-efficacy to entrepreneurial intention has a direct influence. In addition, entrepreneurial outcome expectations and entrepreneurial attitudes also serially mediate the effect of entrepreneurial self-efficacy on entrepreneurial intentions. The originality of this research is the adaptation of Social Cognitive Career Theory into entrepreneurial intention research which is still relatively rare. This research has a theoretical contribution to research on entrepreneurial intentions, which is still dominated by the theory of planned behavior developed by Icek Ajzen.JEL : M20, A22, I20.Keywords : entrepreneurial outcome expectations, entrepreneurial attitude, entrepreneurial intention. ABSTRAKPenelitian ini bertujuan untuk mengetahui serta menganalisis efek mediasi harapan hasil kewirausahaan dan sikap kewirausahaan pada pengaruh efikasi diri kewirausahaan terhadap intensi wirausaha. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei eksplanotori. Adapun alat pengumpulan data penelitian ini menggunakan kuesioner, sedangkan dalam proses penentuan sampel penelitian ini menerapkan teknik convenience sampling sehingga didapatkan 75 orang pemuda di Kecamatan Sukaresik Kabupaten Tasikmalaya. Teknik analisis data yang dilakukan pada penelitian ini Analisis Mediasi Serial Berbasis Pendekatan Regresi dengan menggunakan Software Macro PROCESS yang dikembangkan oleh Andrew F. Hayes. Hasil temuan ini menunjukkan bahwa efikasi diri kewirausahaan berpengaruh secara langsung terhadap intensi wirausaha, selain itu harapan hasil kewirausahaan dan sikap kewirausahaan juga secara serial memediasi pengaruh efikasi diri kewirausahaan terhadap intensi wirausaha. Orisinalitas dari penelitian ini adalah adaptasi Social Cognitive Career Theory ke dalam riset intensi wirausaha yang masih relatif jarang dilakukan. Penelitian ini memiliki kontribusi teoretis dalam riset-riset intensi kewirausahaan yang selama ini masih didominasi oleh theory planned behavior yang dikembangkan oleh Icek Ajzen.